Tim GTLN: a/ A = 2 – x^2 – y^2 – 2(x + y) b/ B = -4x^2 + 4x + 3

Question

Tim GTLN:
a/ A = 2 – x^2 – y^2 – 2(x + y)
b/ B = -4x^2 + 4x + 3

in progress 0
Serenity 2 tháng 2021-07-18T19:48:06+00:00 1 Answers 2 views 0

Answers ( )

    0
    2021-07-18T19:49:46+00:00

    Đáp án:

     a, Ta có : 

    `A = 2 – x^2 – y^2 – 2(x + y)`

    `= -[x^2 + 2(x + y) + y^2 – 2]`

    `= -(x^2 + 2x + 2y + y^2 – 2)`

    `= -[(x^2 + 2x + 1) + (y^2 + 2y + 1) – 4]`

    `= -[(x + 1)^2 + (y + 1)^2] + 4 ≤ 4`

    Dấu “=” xẩy ra

    <=> $\left \{ {{x + 1 = 0} \atop {y + 1 = 0}} \right.$ 

    <=> $\left \{ {{x = -1} \atop {y = -1}} \right.$ 

    Vậy GTLN của A là `4 <=> x = y = -1`

    b, Ta có : 

    `B = -4x^2 + 4x + 3`

    `= -(4x^2 – 4x  – 3)`

    `= -[(2x)^2 – 2.2x.1 + 1 – 4]`

    `= -(2x – 1)^2 + 4 ≤ 4`

    Dấu “=” xẩy ra

    `<=> 2x-  1 = 0`

    `<=> x = 1/2`

    Vậy GTLN của B là `4 <=> x = 1/2`

    Giải thích các bước giải:

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )